2010
DOI: 10.1002/14651858.cd004634.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Follicular flushing during oocyte retrieval in assisted reproductive techniques

Abstract: There is no evidence that follicular aspiration and flushing is associated with improved clinical or ongoing pregnancy rates, nor an increase in oocyte yield. The operative time is significantly longer and more opiate analgesia is required for pain relief during oocyte retrieval. There is a lack of evidence regarding the effect of follicular aspiration and flushing on live birth rates in the identified data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…They found that about 40 % of the oocytes are retrieved with primary aspiration without follicular flushing, while up to 82 % of oocytes are retrieved with two flushes and 97 % of oocytes up to four flushes and only 3 % of the remaining oocytes are retrieved with 5th and 6th flush [18]. In contrast a recent Cochrane review showed that with the utilization of proper retrieval techniques, most of the oocytes are retrieved without the need for follicle flushing [19,20]. However the issue of whether flushing should be not performed is still very much controversial and hotly debated (see discussions posted on www.IVFworldwide.com accessed January and February 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They found that about 40 % of the oocytes are retrieved with primary aspiration without follicular flushing, while up to 82 % of oocytes are retrieved with two flushes and 97 % of oocytes up to four flushes and only 3 % of the remaining oocytes are retrieved with 5th and 6th flush [18]. In contrast a recent Cochrane review showed that with the utilization of proper retrieval techniques, most of the oocytes are retrieved without the need for follicle flushing [19,20]. However the issue of whether flushing should be not performed is still very much controversial and hotly debated (see discussions posted on www.IVFworldwide.com accessed January and February 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, follicular flushing should facilitate oocyte retrieval and should maximize the collection of oocytes [3] [4] [5] [6]. Nevertheless, with the development of oocyte retrieval technology, an increasing number of studies have found that skilled oocyte retrieval by direct aspiration can be used to obtain the vast majority of oocytes.…”
mentioning
confidence: 99%
“…Nevertheless, with the development of oocyte retrieval technology, an increasing number of studies have found that skilled oocyte retrieval by direct aspiration can be used to obtain the vast majority of oocytes. Conversely, the use of a DLN for follicular flushing would prolong the operative time, affect the fertilization of oocytes, and confer no benefit compared with the use of a single-lumen needle (SLN) [6] [7]. A meta-analysis published by Roque et al in 2012 concluded that in an unselected group of patients, there was no advantage in using a DLN in oocyte retrieval [8].…”
mentioning
confidence: 99%
“…There have been several reviews on the effectiveness of follicular flushing in human IVF [11][12][13][14]. A comprehensive Cochrane review performed in 2010 [11] included four prospective randomized controlled trials with a total of 208 patients comparing aspiration alone with aspiration with flushing.…”
mentioning
confidence: 99%
“…A comprehensive Cochrane review performed in 2010 [11] included four prospective randomized controlled trials with a total of 208 patients comparing aspiration alone with aspiration with flushing. Essentially, none of the four studies demonstrated any increase in mean oocytes retrieved or fertilization rates achieved.…”
mentioning
confidence: 99%